LOS HALLAZGOS PAPIRÁCEOS MÁS RECIENTES DE SAFO - Fernández Delgado, José Antonio (Exemplaria Classica, 2018)
Anton Bierl - André Lardinois (edd.). The newest Sappho: P. Sapph. Obbink and P. GC inv. 105, Frs. 1-4. Studies in archaic and classical Greek song, vol. 2. Mnemosyne supplements. Monographs on Greek and Latin language and literature, 392. Leiden-Boston: Brill, 2016, xv+ 543 pp. 223.00. ISBN 978-90-04-31162-6.